Redox-controlled hydrogen bonding: turning a superbase into a strong hydrogen-bond donor - Wild, Ute; Neuhäuser, Christiane; Wiesner, Sven; Kaifer, Elisabeth; Wadepohl, Hubert; Himmel, Hans-Jörg (Chemistry - a European journal, 2014)
Abstract Herein the synthesis, structures and properties of hydrogen-bonded aggregates involving redox-active guanidine superbases are reported. Reversible hydrogen bonding is switched on by oxidation of the hydrogen-donor unit, and leads to formation of aggregates in which the hydrogen-bond donor unit is sandwiched by two hydrogen-bond acceptor units. Further oxidation (of the acceptor units) leads again to deaggregation. Aggregate formation is associated with a distinct color change, and the electronic situation could be described as a frozen stage on the way to hydrogen transfer. A further increase in the basicity of the hydrogen-bond acceptor leads to deprotonation reactions.
Gesehen am 20.08.2020